Evaluation of the Nijmegen Cochlear Implant Questionnaire in Danish - Charlotte Skov Neumann; Jesper Hvass Schmidt (International Archives of Otorhinolaryngology)
Introduction The Nijmegen cochlear implant questionnaire (NCIQ) is a quantifiable self-assessment health-related quality of life (HRQoL) tool used internationally to determine quality of life (QoL) in cochlear implant (CI) users and to evaluate the implant's subjective benefits.